2018
DOI: 10.3390/cancers10040091
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Instability in Hodgkin Lymphoma: An In-Depth Review and Perspectives

Abstract: The study of Hodgkin lymphoma (HL), with its unique microenvironment and long-term follow-up, has provided exceptional insights into several areas of tumor biology. Findings in HL have not only improved our understanding of human carcinogenesis, but have also pioneered its translation into the clinics. HL is a successful paradigm of modern treatment strategies. Nonetheless, approximately 15–20% of patients with advanced stage HL still die following relapse or progressive disease and a similar proportion of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 149 publications
2
29
0
2
Order By: Relevance
“…In this study, only one of our patients (ABVD‐118) had nodular sclerosis subtype, and, interestingly, she showed the highest levels of CA in the BT sample. The high frequency of CA found in in the PBL of HL patients before treatment confirms previous reports showing an increase in chromosomal aberrations in circulating lymphocytes before any treatment (M'Kacher et al, ; Cuceu et al, ). The origin and consequences of this increased basal level of chromosomal damage in HL patients remain to be elucidated.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, only one of our patients (ABVD‐118) had nodular sclerosis subtype, and, interestingly, she showed the highest levels of CA in the BT sample. The high frequency of CA found in in the PBL of HL patients before treatment confirms previous reports showing an increase in chromosomal aberrations in circulating lymphocytes before any treatment (M'Kacher et al, ; Cuceu et al, ). The origin and consequences of this increased basal level of chromosomal damage in HL patients remain to be elucidated.…”
Section: Discussionsupporting
confidence: 89%
“…Hodgkin lymphoma (HL), a malignant disease of the lymphatic system, represents about 10% of all diagnosed lymphoma cases, and only 1% of all cancers in the industrial countries [1]. It is the most commonly diagnosed neoplasm in young adults and it has two incidence peaks, one in the third decade of life and the other after the age of 55 [2].…”
Section: Introductionmentioning
confidence: 99%
“…These subtypes are characterized by the presence of Hodgkin/Reed-Sternberg (HRS) cells, which are large mono-nucleated or multi-nucleated cells with prominent nucleoli [6]. Although HRS cells represent only 1-2% of the tumor burden, they are considered the key marker for HL diagnosis, and they play an important role in the interaction with other immune-modulatory cells in the tumor microenvironment of HL [1,7]. It has been established that HRS cells of cHL originate from the germinal center (GC) B-cells [8].…”
Section: Introductionmentioning
confidence: 99%
“…The evidence of a unique genetic environmental susceptibility in Hodgkin lymphoma (HL) patients has been, and continues to constitute, an important step to understand the complex interplay of factors underlying lymphomagenesis and evolution of this malignant disease (Cuceu et al , Cuceu et al ).…”
mentioning
confidence: 99%
“…Nevertheless, the study of Ramos et al has confirmed the presence of the rogue cells in circulating lymphocytes of HL patients and, hence, launches the discussion on three major points: first the involvement of the viral infection in Hodgkin's lymphoma and the possibility of having another virus playing an important role in the initiation of the disease and of the genomic instability; second, the consistency of HL patients regarding genomic instability; and third the differences observed recently between mixed cellularity and nodular sclerosis HL cell lines and HL patients in term of mechanisms underlying genomic instability (Cuceu et al , Cuceu et al ). Higher frequencies of chromosomal aberrations and in particular of complex chromosomal aberrations were identified in mixed cellularity HL cell lines compared to those observed in nodular sclerosis HL cell lines.…”
mentioning
confidence: 99%